Letter - Brown, W.
001-0197-001 ABERDEEN TRADES COUNCIL (Affiliated to the Scottish Trade Union Congress). Secretary : W. BROWN. Council Rooms & Office : 47 Belmont Street, ABERDEEN. 6th. July, 1936. Sir. Walter Citrine, Transport House, Smith Square, (South Block). London. Dear Sir, My council wish to convey the following information to the Spanish delegates presently attending the IFTU. Your countrymen who man the "S.S "Eolo are somewhat perturbed at their position, the ship is on temporary charter and, they maintain that unless the ship is within Spanish waters with the prescribed period, that is six months from the commencing of the charter, it commenced on January the 15th 1936 (you will therefore see that very little time is left) they shall have forfeited all claim to their wages. I may add that they have been on strike for over a month. I would like if you could acquaint your countrymen if this is correct or otherwise, l am, Yours faithfully, W.Brown. P.S. I append a resolution at a mass meeting of the Aberdeen trade unions. RESOLUTION. " We welcome the delegates of the I.F.T.U. to this country and express our solidarity with all foreign workers and toilers, hoping the maximum amount of unity in the working class movement will take place at the earliest possible moment." I.F.T.U,—International Federation of Trade Unions. ALBION PRESS 292/946/1/197